(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2023)
This article presents experimental investigations into gas cleaning processes within wet dust filtration apparatus. Through a series of experiments, the study explores the dynamics of mass exchange along the length of the liquid film formed in the working pipe. It identifies and analyzes the primary factors influencing the efficiency of the cleaning process in wet vacuum systems. The article emphasizes key elements such as gas flow dynamics, lumped flow phenomena, contact elements, the characteristics of the liquid film, guide angle effects, and various flow regimes, providing comprehensive insights into the nuanced dynamics of gas cleaning mechanisms. The aims - to highlight the experimental focus and the specific factors investigated within the context of gas cleaning in wet dust filtration systems. Adjustments can be made to accommodate any additional details or specific emphases in your study.